The Effects of a Fee-Waiver Program on Health Care Utilization among the Poor : Evidence from Armenia - Chaudhury, Nazmul; Hammer, Jeffrey; Murrugarra, Edmundo (World Bank, Washington, DC, 2014)
This study examines the impact of a fee-waiver program for basic medical services on health care utilization in Armenia. Because of the reduction in public financing of health services and decentralization and increased privatization of health care provision, private out-of-pocket contributions are increasingly becoming a significant component of health costs in Armenia. To help poor families cope with this constraint, the Armenian government provided a free-of-charge basic package service to eligible individuals in vulnerable groups, such as the disabled and children from single parent households. Drawing on the 1996 and 1998-99 Armenia Integrated Survey of Living Standards (AISLS), which allows the identification of eligible individuals under this program, the authors estimate the impact of the fee-waiver program on utilization of health services, particularly among the poor. Across the two survey rounds utilization rates have indeed declined despite comparable levels of income, and this decline has occurred among both the poor and the rich, with average utilization falling by 12 percent between the two surveys. But families with four or more children, the largest beneficiary group under the "vulnerable population" program, have decreased their use of health care services in a disproportionate manner-21 percent reduction in use between the two survey rounds. This precipitous drop in health care use by this vulnerable group, despite being eligible for free medical services, suggests that the program was inadequate in stemming the decline in the use of health services. The authors further present evidence to suggest that the free-of-charge eligibility program acts more like an income transfer mechanism, particularly to disabled individuals.